2019
DOI: 10.3748/wjg.v25.i37.5702
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between Helicobacter pylori infection and irritable bowel syndrome? A meta-analysis

Abstract: BACKGROUNDIrritable bowel syndrome (IBS) is a prevalent and debilitating gastrointestinal condition. Research has reported persistent, low-grade mucosal inflammation and significant overlaps between patients with IBS and those with dyspepsia, suggesting a possible pathogenic role of Helicobacter pylori (H. pylori) in IBS. This study therefore aimed to provide the first systematic review and meta-analysis on the association between H. pylori infection and IBS.AIMTo investigate the association between H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
(38 reference statements)
2
8
1
3
Order By: Relevance
“…A meta-analysis by L MR et al (41) suggested that H. pylori infection rates in IBS patients were significantly higher than expected in a healthy population. However, a similar meta-analysis by Ng et al (42) showed that there was no clear evidence to support an association between IBS and H. pylori; however this may be attributed to the smaller sample size in this study. Our results suggest that anti-H. pylori treatment could reduce IBS symptoms, and this may be mediated by the effects of anti-H. pylori treatments on gastrointestinal pH and flora changes, thereby promoting the recovery of the intestinal mucosal immune system and the gut-brain axis and restoring the regulation of the gastrointestinal hormone system (32).…”
Section: ' Discussioncontrasting
confidence: 76%
“…A meta-analysis by L MR et al (41) suggested that H. pylori infection rates in IBS patients were significantly higher than expected in a healthy population. However, a similar meta-analysis by Ng et al (42) showed that there was no clear evidence to support an association between IBS and H. pylori; however this may be attributed to the smaller sample size in this study. Our results suggest that anti-H. pylori treatment could reduce IBS symptoms, and this may be mediated by the effects of anti-H. pylori treatments on gastrointestinal pH and flora changes, thereby promoting the recovery of the intestinal mucosal immune system and the gut-brain axis and restoring the regulation of the gastrointestinal hormone system (32).…”
Section: ' Discussioncontrasting
confidence: 76%
“…Similar to our findings, individuals with IBS had increased likelihood of H. pylori infection in a recent meta-analysis by Ng QX et al, though there was no statistical significance (OR: 1.47, 95% CI: 0.90-2.40) [33]. Compared to that meta-analysis, there were some differences of search methods and inclusion criteria in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Our results (pooled OR 1.32, 95% CI: 0.94–1.87, P = .11) are very similar to those recently published by Ng et al [ 40 ] (pooled OR 1.47, 95%CI: 0.90–2.40, P = .123). Compared with their study, we conducted subgroup analysis, which showed a very positive correlation between IBS patients diagnosed in Rome III and H pylori infection and there was a negative correlation with H pylori infection in patients with IBS on the non-Roman III diagnostic criteria, the difference between the two groups was statistically significant ( P = .03).…”
Section: Discussionsupporting
confidence: 92%